Validity and Reliability of the Knowledge, Attitudes and Practices Instrument Regarding Monkey Pox in Peru - Yupari-Azabache IL; Díaz-Ortega JL; Bardales-Aguirre LB; Barros-Sevillano S; Paredes-Díaz SE (Dove Medical Press, 2023)
Irma Luz Yupari-Azabache,1 Jorge Luis Díaz-Ortega,1,2 Lucía Beatriz Bardales-Aguirre,3 Shamir Barros-Sevillano,1,4 Susana Edita Paredes-Díaz1 1Grupo de Investigación en Enfermedades Infecciosas y Transmisibles, Universidad César Vallejo, Trujillo, Perú; 2Escuela Profesional de Nutrición, Universidad Cesar Vallejo, Trujillo, Perú; 3Departamento de Ciencias, Universidad Privada del Norte, Trujillo, Perú; 4Sociedad Científica de Estudiantes de Medicina de la Universidad César Vallejo, Trujillo, PerúCorrespondence: Irma Luz Yupari-Azabache, Universidad César Vallejo, Av. Larco 1770, Trujillo, 13009, Perú, Tel +51964612831, Email IYUPARI@ucv.edu.peObjective: To analyze the questionnaire of the validity and reliability of knowledge, attitudes and practices concerning Mpox.Methods: This was an instrumental, cross-sectional study. The sample consisted of 178 citizens from 3 sectors of Peru, who responded to a virtual questionnaire regarding knowledge, attitudes and practices concerning Mpox. The validity and reliability process of the questionnaire was carried out using Aiken's V, Cronbach's Alpha, McDonald's Omega and principal component analysis.Results: After expert evaluation, the questionnaire was shown to have adequate content validity for measuring knowledge, attitudes and practices concerning Mpox, each in their respective dimensions, with Aiken's V values above 0.90. For construct validity, exploratory factor analysis was used and the items were grouped into four dimensions for the level of knowledge, three dimensions for attitudes, and two for practices. With respect to the reliability analysis, the application of Cronbach's α statistic and McDonald's ω, obtained values above 0.70.Conclusion: The results of the research enabled the attainment of a questionnaire that meets the adequate psychometric characteristics in order to be applied.Keywords: validity, reliability, monkey pox, Peru